Tren Penelitian Implementasi Prinsip ESG dalam Praktik Akuntansi : Systematic Literature Review - Miftahul Mubin; Emy Wahyu Utami; Saipul Ami Muhsyaf (Universitas Mataram, 2023)
The performance of a company is not only measured by financial ratios alone; the company's contribution to the environment and the well-being of the surrounding community is also part of determining whether its performance is good or bad. This research is a literature study with a descriptive qualitative research approach, utilizing library research to describe the role of implementing ESG (Environmental, Social, and Governance) principles in accounting practices. The author used various written sources such as articles, journals, and relevant documents pertaining to the subject of this research. Data collection techniques involved using the Publish or Perish (PoP) application, which conducted searches in the Google Scholar database. The Vosviewer software provided three visualization displays in bibliometric analysis: network, overlay, and density visualization. Several challenges arise in implementing ESG principles in accounting practices. Some of these challenges include difficulties in measuring and disclosing relevant ESG aspects, lack of consistent reporting standards, and internal resistance within companies towards change. In some cases, there may be a gap between a company's commitment to ESG and its actual implementation in accounting practices. Despite the challenges faced, implementing ESG principles in accounting practices also brings several benefits to the company. Furthermore, ESG implementation can assist companies in achieving their overall goals and objectives.